Optimal parameters of shock tubes to simulate the high explosive effect of a blast - Chernyshov Mikhail V.; Savelova Karina E.; Yatsenko Anna A. (MATEC Web of Conferences, 2024)
The problem of generating pressure waves with a profile similar to the profile of a blast wave in closed shock tubes with constant cross-section is considered. Applying non-stationary gas dynamics methods, the dimensions (lengths) of high and low pressure chambers are determined analytically and numerically. Also, the gas parameters in those chambers necessary to produce pressure waves with a profile close to triangular are determined.